IDENTIFIKASI KARAKTERISTIK RUANG KREATIF DALAM MENDUKUNG KOTA KREATIF: STUDI KASUS KOTA BANDUNG - Ardiansyah, Dwiki Gamas; Adharina, Nabilla Dina; Iscahyono, Achmad Fauzan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2024)
Bandung City exemplifies this as part of the UNESCO Creative Cities Network. While the government establishes creative spaces like the Bandung Creative Hub, organic community-driven spaces also thrive. Each space possesses unique characteristics, but ideal creative spaces should meet criteria related to institutional support, flexible regulations, and diverse human resources. This mixed-methods study aims to identify the characteristics of Bandung's creative spaces based on institutional, regulatory, and human resource aspects. Qualitative data from interviews will be quantitatively assessed to compare with ideal criteria. Understanding these characteristics can inform urban planning and policy for fostering creative economies. Furthermore, creative space is also believed that it can foster creativity, innovation, and knowledge-based economic growth.